Curriculum as cultural construction: emerging visions in uncertain scenarios (Revista Electrónica REDINE, 2021)
The purpose of this article is to generate reflections on the curricular visions for the development of educational proposals in changing, complex and uncertain scenarios from the perspective of the curriculum as a cultural construction. At present, humanity is going through times far from certainty, the pandemic has shown that the uncertain and complex is perennially in our lives, it changes and transforms our times and spaces, with education being one of the dimensions most affected by said situation. In this sense, we reflect on the possibility of an operationalized education in a curriculum in and for uncertainty based on the premise of curricular innovation from the praxis and the vision of the cultural construction of the curriculum proposed from the theoretical by Shirley Grundy (1991) and the practical by Nelson Lopez (2002). Describing the ideal of the Man formed through emerging curricular proposals for complex educational settings
Keywords: curriculum; proposal educational; cultural construction; curricular visions; uncertainty